Quasiprobability distribution functions for periodic phase spaces: I. Theoretical aspects - Ruzzi, M.; Marchiolli, M. A.; da Silva, E. C.; Galetti, D. (Iop Publishing Ltd, 2006)
An approach featuring s-parametrized quasiprobability distribution functions is developed for situations where a circular topology is observed. For such an approach, a suitable set of angle - angular momentum coherent states must be constructed in an appropriate fashion.